Efeito de estratégias de nutrição comportamental no comportamento alimentar e fatores associados: uma revisão sistemática - Figueiredo, Flaviane Scheeren (2023)
Nutritional transition has occurred globally in recent decades as a result of social transformations and economic growth, generating significant changes in dietary patterns and body composition. These changes have been associated with the emergence of chronic diseases, such as obesity, being a risk factor for comorbidities such as dyslipidemia, diabetes mellitus and cardiovascular diseases. In this context, it is essential to promote changes in eating habits, and traditional dietary education emphasizes restricting energy intake to control weight. However, in the long run, the results of weight loss diets are limited, requiring alternatives to the usual restrictive diet. Thus, behavioral nutrition emerges as a promising approach to improve eating behavior and population health. This strategy emphasizes the relationship between the individual and food, taking into account not only physiological factors, but also emotional and social factors that influence choices. Within the behavioral nutrition approach, nutritionists can use several tools and strategies in order to promote changes, facilitating communication that generates bonds, trust and respect. The aim of this study was to evaluate the effect of behavioral nutrition interventions on eating behavior and associated factors. This is a systematic review carried out in PubMed, SciELO and Lilacs databases. Studies published from 2018 onwards, including adults of both sexes, were selected. A total of 1,132 articles were identified and 26 were included in this review after applying the eligibility criteria, 12 of which were randomized clinical trials, 12 intervention studies, and two mixed methods studies. The studies were carried out, for the most part, in the United States of America and Brazil. The target audience was mostly overweight adults. Seven of the studies were conducted exclusively with women. The most frequently used strategy in the interventions was mindfulness, present in 14 articles, followed by intuitive eating (n=7) and motivational interview (n=6). Most studies had positive results, showing behavioral nutrition interventions as promoters of changes in eating behavior, as well as a reduction in caloric intake and improvement in diet quality. In addition, a decrease in weight and body mass index and in waist circumference, as well as in laboratory parameters, was observed. Regarding psychological variables, there was a significant improvement in levels of depression, stress, eating disorders and body self-esteem. The results obtained in this review suggest, for the most part, an improvement in eating behavior, especially in overweight and obese individuals. The adoption of behavioral nutrition strategies seems to be favorable in this context, promoting more conscious eating and reducing inappropriate eating habits.